Euroscepticist tendencies of the populist parties in France : a study on “National Rally” and ”France Unbowed” - Sezer, Aslıcan (My University, 2019)
Son yıllarda Avrupa bütünleşmesi ve Avrupa Birliği’ne (AB) artan karşıtlık, Avrupakuşkuculuğunu Avrupa siyasetinin temel bir olgusu olarak dikkate almayı gerektirmektedir.Avrupa kuşkuculuğunun ilk olarak 1980’lerde akademik alanda ve medyada kullanılmayabaşlandığı görülmektedir. Diğer yandan, önceki dönemlere kıyasla daha ileri bir bütünleşmeyihedef alan Maastricht Antlaşması, Avrupa kuşkuculuğu tarihinde bir dönüm noktası olarakkabul görmektedir. Ayrıca bu çalışma, Brexit süreci ve Mayıs 2019 Avrupa Parlamentosuseçimleri gibi Avrupa siyasetindeki önemli gelişmelerin gerçekleştiği bir dönemdehazırlanmıştır. Avrupa bütünleşmesine kuşkucu yaklaşan siyasi partilerin başarılarındaki vebu tür partilere ilgideki artış, partilerin Avrupa siyasetindeki etkilerini sorgulamayıgerektirmektedir. Siyasi partilerin temsili demokrasilerdeki görevleri, parti merkezli Avrupakuşkuculuğunun önemini arttırmaktadır. Siyasi partilere dayalı Avrupa kuşkuculuğunaodaklanan bu tez, Fransa’dan farklı ideolojilere sahip iki popülist partinin, Ulusal Birlik veBoyun Eğmeyen Fransa, Avrupa bütünleşmesi üzerine benzer ve farklı tutumlarını konuedinmektedir. İdeolojilerin partilerin üzerindeki azalan etkisi ve ana akım partiler arasındakibenzerliklerin artışı göz önüne alındığında, günümüzün bir diğer önemli olgusu olanpopülizm, Avrupa kuşkuculuğun yükselişine kapsamlı bir açıklama sunmaktadır.

In recent years, the increasing opposition to European integration and European Union (EU)necessitates considering Euroscepticism as a fundamental phenomenon of European politics.It is seen that Euroscepticism has been firstly used in the academic field and media in the1980s. On the other hand, the Maastricht Treaty that aims further integration compared to theprevious period is accepted as a turning point in the history of Euroscepticism. Also, thisstudy coincides with crucial developments in European politics such as unresolved Brexitprocess and May 2019 European Parliament elections. The increasing success of Euroscepticparties and public attention to such parties require the interrogation of their effect in Europeanpolitics. Party-based Euroscepticism has an important place due to political parties’ roles inrepresentative democracies. This thesis that is focused on party-based Euroscepticismexplains the similar and different Eurosceptic attitudes of the two populist political parties,National Rally and France Unbowed, with different ideologies in France. Given thedecreasing effect of ideologies in political parties’ stances and increasing similarities betweenestablished parties, populism as another important phenomenon of today’s politics, provide aninclusive explanation to the rise of Euroscepticism.
Keywords: Avrupa Birliği; Avrupa Bütünleşmesi; Avrupa Kuşkuculuğu; European Union; Euroscepticism; Political Party; Politics, Practical; Politika, Uygulamalı; Populism; Popülizm European Integration; Siyasi Parti